Parental support in undergraduate students' English language learning - Tan, Arvina Siaw Hui. (Universiti Malaysia Sarawak (UNIMAS), 2007)
This study aims to explore perceived parental support in undergraduate students' English language learning. A total of 205 undergraduate students at one of the local universities in Malaysia were involved in this study. The study was designed as a quantitative survey whereby questionnaires were utilized as instrument of data collection. The findings of this study revealed most of the participants' parents have positive attitudes towards their English language learning regardless of parents' educational background. Most of the parents played their role as collaborators with teachers in participants' English language learning. However, most of the participants perceived parents as language learning facilitators contribute most t(!) their English language learning. The evidence suggests that the ways in which parents support their children in English language learning are particular important as it may affect the development of the children as language learners.